Metabolite profile changes and increased antioxidative and antiinflammatory activities of mixed vegetables after fermentation by Lactobacillus plantarum. - Jungyeon Kim; Kum-Boo Choi; Ju Hun Park; Kyoung Heon Kim (PLoS ONE, 2019)
Fermented vegetables have emerged as prebiotics with various health benefits. However, the possible mechanisms behind their health benefits are unclear. To relate the metabolite profile changes in fermented mixed vegetables with associated health benefits of fermented vegetables, we analyzed the metabolite profiles of mixed vegetables, before and after fermentation by Lactobacillus plantarum, using gas chromatography/time-of-flight-mass spectrometry (GC/TOF-MS). To analyze health benefits of fermented vegetables, antioxidative and antiinflammatory activities were measured using RAW 264.7 cells. Among 78 metabolites identified by GC/TOF-MS in this study, those significantly increased after fermentation include antioxidative and/or antiinflammatory agents such as lactate, 3-phennyllactate, indole-3-lactate, β-hydroxybutyrate, γ-aminobutyrate, and glycerol. These metabolites may have been either newly synthesized or depolymerized from high molecular weight polymers from vegetables during fermentation. This is the first metabolomics study to relate metabolite profile changes with increased health benefits of fermented vegetables.